(untitled) (London Journal of Medical and Health Research, 2025)
Introduction: Severe thoracic trauma is the second leading cause of death in multiple traumas after head trauma. The objective of this study is to research the serious factors of thoracic trauma at the Joseph Ravoahangy Andrianavalona Antananarivo university hospital center. Patients and methods: This is a retrospective cohort study on patients with closed and open chest trauma hospitalized in the thoracic surgery department, from January 1, 2015, to December 31, 2022. Results: We had collected 331 patients with a male predominance (82.2%), with the median age of 29 years, many of our patients were treated by chest drainage (62.8%), and 17.2% having received a thoracotomy. The mortality rate is 36.2%. Several factors were found: age ≥ 55 years (RR=2.7 [2.2-3.4]), chronic respiratory disease including : obstructive pulmonary disease, asthma (RR=2.8 [2.3-3 ,4]), the comatose state (RR=2.1[1.6 -2.8], hemodynamic instability and respiratory distress syndrome; patient victim of penetrating trauma and associate neurological lesion ; l severe anemia ≤ 70g/l (RR=2.4 [1.7-3.1]); chest flap, compressive pneumothorax (RR=5.5 [2.5-6.7]) and large hemothorax ≥ 1500 ml (RR=3.6 [2.4-5.4]; delay in management beyond six hours (RR=2.1 [1.6-2.8]), massive blood transfusion; Chest tube flow ≥ 250 ml/h. Conclusion: Serious thoracic trauma leads to a high mortality rate, several factors have been implicated, clinical, biological, scannographic and therapeutic factors.